2022
DOI: 10.1111/jnu.12819
|View full text |Cite
|
Sign up to set email alerts
|

Clinical indicators of acute deterioration in persons who reside in residential aged care facilities: A rapid review

Abstract: Purpose: To identify the clinical indicators of acute deterioration in residents and the factors that influence residential aged care facility staff's identification of these.Design: Rapid review and narrative synthesis. Methods:The WHO and Cochrane Rapid Review Methods Group recommendations guided the review processes. CINAHL, Medline, PubMed, and the Cochrane Library were searched from 2000 to January 2022. Data related to clinical indicators of deterioration were categorized using the Airway, Breathing, Cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…However, staff skills and confidence are over-estimated. Chambers et al (2023) highlighted that staff confidence is vital to identifying acute deterioration in residents. This evaluation found that despite training, some staff lacked the confidence to take observations and were not prepared for the challenges of taking observations in a setting with residents who may be unwell, agitated or uncooperative.…”
Section: Discussionmentioning
confidence: 99%
“…However, staff skills and confidence are over-estimated. Chambers et al (2023) highlighted that staff confidence is vital to identifying acute deterioration in residents. This evaluation found that despite training, some staff lacked the confidence to take observations and were not prepared for the challenges of taking observations in a setting with residents who may be unwell, agitated or uncooperative.…”
Section: Discussionmentioning
confidence: 99%